A case report on Port-a-Cath related bacteremia with Pantoea species in a cancer patient - Rinki Kundu; Najeeb Mahiyuddin; Rajib Bhadra; Afsana Begum (Bangladesh Critical Care Journal, 2023)
Pantoea species are gram negative rods that rarely effects human. They usually cause infection in immunocompromised hosts. The cause is usually due to trauma by vegetative material or contamination of medical devices. Here we report a case of bacteremia due to Pantoea species in patient with malignancy having a Port-a-Cath. The infection was detected by blood culture from both chemo port and peripheral line. The clinical outcome was good with intravenous antibiotics and chemo port removal. Bangladesh Crit Care J September 2023; 11 (2): 127-129